To complete the table for the function \( f(x) = -(x - 1.4)^2 + 6 \), we will calculate the value of \( f(x) \) for each value of \( x \) provided.
-
For \( x = 0 \): \[ f(0) = - (0 - 1.4)^2 + 6 \] \[ = - (1.96) + 6 \] \[ = 6 - 1.96 = 4.04 \]
-
For \( x = 1 \): \[ f(1) = - (1 - 1.4)^2 + 6 \] \[ = - (-0.4)^2 + 6 \] \[ = - (0.16) + 6 \] \[ = 6 - 0.16 = 5.84 \]
-
For \( x = 2 \): \[ f(2) = - (2 - 1.4)^2 + 6 \] \[ = - (0.6)^2 + 6 \] \[ = - (0.36) + 6 \] \[ = 6 - 0.36 = 5.64 \]
-
For \( x = 3 \): \[ f(3) = - (3 - 1.4)^2 + 6 \] \[ = - (1.6)^2 + 6 \] \[ = - (2.56) + 6 \] \[ = 6 - 2.56 = 3.44 \]
Now we can summarize the results in the completed table:
\[ \begin{array}{|c|c|} \hline x & f(x) \ \hline 0 & 4.04 \ 1 & 5.84 \ 2 & 5.64 \ 3 & 3.44 \ \hline \end{array} \]